EVALUATION OF NORMALIZED DIFFERENCE VEGETATION INDEX IN WILD APPLE POPULATIONS GROWING IN SOUTHEAST MOUNTAIN REGIONS OF KAZAKHSTAN - Taskuzhina, A.; Khusnitdinova, M.; Kerimbek, N.; Kapytina, A.; Pozharskiy, A.; Moisseyev, R.; Gritsenko, Dilyara (Eurasian Journal of Applied Biotechnology, 2024)
NDVI is one of the most common vegetation indices for solving various problems of assessing the state of vegetation cover and its dynamics. The purpose of the study was to evaluate the state of wild Sievers apple trees in the territory of Phenological area, Genetic Reserve of Sievers, Tauturgen and Sievers apple reserve (Zhongar-Alatau and Ile-Alatau SNNP) using the NDVI index. The period of study was season’s autumn 2022 and spring 2023. Created interactive maps of the study area with multispectral reconstructions in NDVI formats let us was established the condition of the Sievers apple tree. Which was based on an analysis of the deviation of the NDVI of each tree in the study area from the average index value for the vegetation of the entire type of area. This allowed us to identify the territorial features of the state of the Sievers apple trees and identify degraded trees. The results obtained can be used for the rational management of environmental management by the Zhongar-Alatau SNNP and the Ile-Alatau SNNP.